FUNCTIONAL PRO GROUP FOR SENIOR ADULTS - Ordozgoite Coelho Joaquim da Silva, Lucas; de Almeida Ribeiro, Mateus (Health and Society, 2023)
As we know, nowadays we see a much younger audience in gyms, crossfit, functional and other means of maintaining health in practice. and we observe that today the number of elderly people is growing to become part of the majority who practice healthy activities, many think they don’t need it and even think it’s unnecessary, but for this age group it is extremely important that they don’t stand still, as it can be harmful to their health, examples: Heart disease and stroke, among others. The functional aims to prepare the elderly for daily activities, preventing them from injuries, delaying aging and avoiding chronic diseases such as hypertension, obesity and diabetes, common in old age. This training arose with the aim of working on all the functionalities of the human body. Functioning in the sand helps mainly with Motor Coordination, Flexibility, Balance, upper and lower limbs and trunk.